2011
DOI: 10.1177/0093854811400823
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Pretrial Publicity

Abstract: The authors investigated the effects of exposure to pretrial publicity (PTP) on impression formation, juror emotion, and predecisional distortion. Mock jurors read news articles containing negative (antidefendant) PTP or positive (prodefendant) PTP or unrelated articles. One week later, they viewed a videotaped murder trial and then made decisions about guilt. Jurors’ emotions were measured three times during the experiment: before exposure to PTP, immediately after exposure to PTP, and immediately following t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…Others have treated a discrete, ordinal independent variable as interval level and used standard regression-based techniques (Chandler & Pronin, 2012;Legault, Gutsell, & Inzlicht, 2011). Alternatively, investigators have modified their data to produce a dichotomous X, such as by conducting separate analyses comparing various groups of interest while discarding the remaining data (Pedersen, Denson, Goss, Vasquez, Kelly, & Miller, 2011;Ronay, Greenaway, Anicich, & Galinsky, 2012;Werle, Wansink, & Payne, 2011;Whitchurch, Wilson, & Gilbert, 2011) or collapsing multiple groups into one for comparison with another group or set of groups (Calogero & Jost, 2011;Haisley & Loewenstein, 2011;Ruva, Guenther, & Yarbrough, 2011). Another strategy used is substituting a continuous manipulation check for the multicategorical X and proceeding with a mediation analysis as if X were observed as a continuum (Forgas, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Others have treated a discrete, ordinal independent variable as interval level and used standard regression-based techniques (Chandler & Pronin, 2012;Legault, Gutsell, & Inzlicht, 2011). Alternatively, investigators have modified their data to produce a dichotomous X, such as by conducting separate analyses comparing various groups of interest while discarding the remaining data (Pedersen, Denson, Goss, Vasquez, Kelly, & Miller, 2011;Ronay, Greenaway, Anicich, & Galinsky, 2012;Werle, Wansink, & Payne, 2011;Whitchurch, Wilson, & Gilbert, 2011) or collapsing multiple groups into one for comparison with another group or set of groups (Calogero & Jost, 2011;Haisley & Loewenstein, 2011;Ruva, Guenther, & Yarbrough, 2011). Another strategy used is substituting a continuous manipulation check for the multicategorical X and proceeding with a mediation analysis as if X were observed as a continuum (Forgas, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Even after many decades of research on juror/jury decision making, the effects of PTP on deliberating jurors are still unclear (Daftary-Kapur, Dumas, & Penrod, 2010). Previous research has found that PTP imparts its biasing effects on jurors' decisions by influencing their perceptions of the defendant's credibility and their ability to discriminate the source of case information (PTP vs. trial; Ruva & McEvoy, 2008;Ruva, McEvoy, & Bryant, 2007), as well as eliciting emotional responses in jurors (Kramer, Kerr, & Carroll, 1990;Ruva, Guenther, & Yarbrough, 2011), and causing predecisional distortion (Hope, Memon, & McGeorge, 2004;Ruva, Mayes, Dickman, & McEvoy, 2012).…”
mentioning
confidence: 99%
“…In support of this finding, Ruva, McEvoy & Bryant (2007) found that exposure to negative pre-trial publicity significantly affected the number of guilty verdicts, the sentence length awarded and perceptions of defendant credibility. While Ruva, Guenther & Yarbrough (2011) found that mock jurors exposed to positive pre-trial publicity were significantly more likely to vote not guilty and rate the defendant as more credible, compared to jurors exposed to negative pre-trial publicity and jurors who were not exposed to pre-trial publicity.…”
Section: Pre-trial Publicity: Negative and Positivementioning
confidence: 87%